Extracellular Vesicles and PD-L1—A Review of Complex Immunoregulatory Properties and Clinical Importance - Kajetan Kiełbowski; Paulina Plewa; Jacek Szulc; Maciej Ćmil; Estera Bakinowska; Andrzej Pawlik (Biomedicines, 2025)
Extracellular vesicles (EVs) are membrane-bound structures released by cells that contain bioactive cargo such as cytokines or non-coding RNA. It is widely known that EVs influence the activity of other cells; they take part in the pathogenesis and compensatory mechanisms of multiple diseases. Frequently, EVs can share the properties of their source cells, thus allowing the use of EVs as non-cellular vectors or therapeutic agents. Importantly, these structures can express the ligand for the programmed cell death protein 1 (PD-L1). It binds to the PD-1 protein present on the immune cells, which suppresses the activity of T cells. The PD-1/PD-L1 axis is widely known in the field of oncology, as PD-L1 present on the surface of cancer cells inhibits cytotoxic activity of T cells, thus promoting cancer growth and treatment resistance. Immunotherapy prevents PD-1/PD-L1 binding and restores anticancer properties of the immune cells. By contrast, the above-mentioned binding is desired in the context of autoimmunity, where abnormal activity of immune cells is a hallmark element in the pathogenesis of these conditions. The aim of this review is to present and discuss the latest findings regarding the role of EVs-PD-L1 in cancer and autoimmunity.